Lalatabimba on the Garbhagriha entrance of the Shiva Temple 2 - Temples of India Project Team (Jio Institute, 2024)
The lalatabimba (lintel) on the garbhagriha (sanctum sanctorum) entrance of the Shiva Temple (Shiva Temple 2) features a seated Lakulisa within a small niche. Lakulisa is depicted in padmasana (lotus pedestal pose) with two arms, holding a phala (fruit) and a danda (staff). On either side, Gandharva (celestial musicians) couples are illustrated holding garlands. The uttaranga (top horizontal band of the architrave) of the temple showcases depictions of Matrikas, Veerabhadra, along with Ganesha and Brahma.